Faktor Yang Mempengaruhi Perilaku Bidan Terhadap Pencegahan HIV/AIDS Dalam Pertolongan Persalinan Normal di RSKDIA Siti Fatimah dan RSKDIA Pertiwi Makassar Tahun 2020: Factors Influencing Midwife's Behavior towards HIV/AIDS Prevention in Normal Childbirth Assistance at Siti Fatimah Hospital and Makassar Pertiwi Hospital in 2020 - MS, Nur Hidayah (Jurnal Ilmiah Amanah Akademika, 2020)
HIV/AIDS behaviors or precautions are important for midwives who help with childbirth. Non-standard HIV/AIDS prevention measures are not only risky to patients but are very dangerous for midwives because of the higher risk of exposure to pathogenic germs occurring in the delivery room. The research method used is an analytical survey with a cross sectional study approach. The sample was a midwife who served in the delivery room and performed normal childbirth assistance for 36 people. The sampling technique used is purposive sampling. Based on the results of the analysis with the Chis Quare test, ρ=0.027 < α=0.005 and ρ=0.000 < α=0.005 which means that Ho is rejected and Ha is accepted and ρ=0.446 > α=0.005 which means Ho is accepted and Ha is rejected. Thus there is an influence of attitudes and length of service with midwife behavior on HIV / AIDS prevention on normal childbirth assistance, there is no influence of education level with midwife behavior on HIV / AIDS prevention on normal childbirth assistance.